Mining of Resistance Gene Analogues for Anthracnose Disease in Greater Yam ( Dioscorea alata L.) - Saranya, G; Nath, Vishnu S; Jeeva, M L; Sheela, M N; Makeshkumar, T (JOURNAL OF ROOT CROPS, 2017)
Nucleotide-binding site- leucine-rich repeat (NBS- LRR) gene family holds the vast majority of resistance genes identified in plants. Primers based on the conserved motifs were used to isolate NBS type sequences in tolerant and susceptible greater yam ( Dioscorea alata ) cultivars. Cloning and sequencing of identified NBS-type sequences called resistance gene analogues (RGAs) depicted similarity to other cloned RGA sequences available in the public database. The deduced amino acid sequences of the RGAs showed the presence of conserved domains, viz. P-loop, RNBS-B, RNBS-C, Kinase-2 and GLPL, categorising them with the NBS.LRR class gene family. Amino acid sequence alignment of the Dioscorea RGAs with RGAs of other plant species grouped them with the non-toll interleukin receptor subclasses of the NBS sequences. The sequence comparison of RGAs in susceptible and tolerant variety showed very little difference between them. This study represents the first report of isolation and characterisation of RGAs from Dioscorea alata and will act as a stepping stone for future studies aiming at identifying candidate anthracnose resistance genes in Dioscorea spp.